Atomically Dispersed Mo Supported on Metallic Co9S8 Nanoflakes as an Advanced Noble‐Metal‐Free Bifunctional Water Splitting Catalyst Working in Universal pH Conditions. Issue 4 (11th December 2019) - Wang, Ligang; Duan, Xinxuan; Liu, Xijun; Gu, Jing; Si, Rui; Qiu, Yi; Qiu, Yaming; Shi, Dier; Chen, Fanhong; Sun, Xiaoming; Lin, Jianhua; Sun, Junliang
Abstract: Water splitting requires development of cost‐effective multifunctional materials that can catalyze both the hydrogen evolution reaction (HER) and the oxygen evolution reaction (OER) efficiently. Currently, the OER relies on the noble‐metal catalysts; since with other catalysts, its operation environment is greatly limited in alkaline conditions. Herein, an advanced water oxidation catalyst based on metallic Co9 S8 decorated with single‐atomic Mo (0.99 wt%) is synthesized (Mo‐Co9 S8 @C). It exhibits pronounced water oxidization activity in acid, alkali, and neutral media by showing positive onset potentials of 200, 90, and 290 mV, respectively, which manifests the best Co9 S8 ‐based single‐atom Mo catalyst till now. Moreover, it also demonstrates excellent HER performance over a wide pH range. Consequently, the catalyst even outperforms noble metal Pt/IrO2 ‐based catalysts for overall water splitting (only requiring 1.68 V in acid, and 1.56 V in alkaline). Impressively, it works under a current density of 10 mA cm −2 with no obvious decay during a 24 h (0.5 m H2 SO4 ) and 72 h (1.0 m KOH) durability experiment. Density functional theory (DFT) simulations reveal that the synergistic effects of atomically dispersed Mo with Co‐containing substrates can efficiently alter the binding energies of adsorbed intermediate species and decrease the overpotentials of the water splitting. Abstract : Novel precious‐metal free Mo single‐atom bifunctional catalysts can catalyse the oxygen evolution reaction, hydrogen evolution reaction, and overall water splitting reactions in pH‐universal conditions. Furthermore, the reported Mo‐Co9 S8 @C sample exhibits the best durability for a given activity over a wide pH range (acid, base, and neutral) among all reported catalysts. Consequently, the bifunctional Mo‐Co9 S8 @C catalyst outperforms noble metal Pt/IrO2 ‐based catalysts for overall water splitting.